Prospects for the application of battery energy storage systems in NPP auxiliary power supply systems - V. V. Karchin; I. V. Meldin; A. N. Pitev (Глобальная ядерная безопасность)
One of the characteristics of energy strategy, which currently implementing is atomic energy elaboration and NPP development with rising part of atomic generation in national energy system. Of course one of the most important property of atomic generation is safety (Chernobyl, Three Mile Island, Fukushima Daiichi accidents). To maintain the operation of security systems in conditions of loss of external power supply, autonomous power sources - diesel-generator sets are used, but their use is associated with a number of difficulties of operation and maintenance, and currently developing technologies allow to realize new processes of energy transformation. And on the other hand modern technologies are providing access to new energy saving technologies. In this article we will try to compare energy storage systems, which use different physical principles and try to review their advantages and particularities. Also we especially explore operational advantages of battery energy storage systems and their influence on atomic safety and maintenance cycles and also integrating to digital control system and more effective generation and flexibility during NPP operation with conclusion about new business for «Rosatom» company.